When the bite is not the threat: non-venomous snakebites and their impact on rural child health - Kavinda Dayasiri; Achila Ranasinghe; Nayani Suraweera; Priyanga Burhan (BMJ Paediatrics Open, 2025)
Background While the clinical management of venomous snakebites has been widely studied, little attention has been paid to paediatric bites from non-venomous or mildly venomous snakes in Sri Lanka. Although medically less severe, these bites frequently lead to healthcare visits and even hospital admissions, primarily due to caregiver anxiety and concern, and may result in minor complications.Methods A multicentre descriptive cross-sectional study was conducted across four referral hospitals in Sri Lanka. Children aged 0–17 years with confirmed bites from snakes of low or no medical significance were included. Data were collected through medical records and caregiver interviews. A matched control group was used to explore environmental and behavioural risk factors. Multivariate logistic regression identified independent predictors of snakebites.Results Among 183 children, the mean age was 10.5 years (SD=4.1), with 68.3% being male. Most lived in rural areas (86.9%), and rat snakes and water snakes were the most frequently implicated species. Bites primarily affected the feet (71%) and occurred during outdoor activities at home. Most children presented to healthcare facilities within 1 hour of the bite. Multivariate analysis showed that regular use of a torchlight (OR: 0.38, p<0.001) and home garden cleaning (OR: 0.35, p<0.001) were protective, while the presence of rats (OR: 2.01, p<0.001) and proximity to water bodies (OR: 1.92, p=0.04) were associated with increased risk.Conclusion Non-venomous and mildly venomous snakebites in children are common in rural Sri Lanka and are influenced by modifiable behavioural and environmental factors. Targeted community education and preventive measures could reduce unnecessary health system burdens